Trajectories of terminally ill patients' cardiovascular response to receptive music therapy in palliative care - Warth, Marco; Keßler, Jens; Hillecke, Thomas; Bardenheuer, Hubert J. (Journal of pain and symptom management, 2016)
Context Relaxation interventions are frequently used to promote symptom relief in palliative care settings, but little is known about the underlying mechanisms. Objectives The present analysis aimed at examining the psychophysiological pathways of terminally ill patients' cardiovascular response to a live music therapy vs. prerecorded mindfulness exercise. Methods Eighty-four patients of a palliative care unit were randomly assigned to either of the two interventions. Multilevel modeling was used to analyze trajectories of physiological change. Vagally mediated heart rate variability (VM-HRV) and blood volume pulse amplitude (BVP-A) served as indices of autonomic nervous system response. Participants' gender, age, baseline scores, self-rated pain, and assignment to treatment were entered to the models as predictors. Results Both VM-HRV and BVP-A showed significant linear and quadratic trends over time, as well as substantial heterogeneity among individuals' trajectories. Baseline scores, pain, and treatment significantly accounted for random variation in VM-HRV intercepts. BVP-A levels were significantly higher in women than in men. Moreover, assignment to treatment significantly accounted for differences in the linear slopes of peripheral blood flow. Conclusion Higher levels of VM-HRV in the music therapy group highlight the importance of a therapeutic relationship for the effectiveness of relaxation interventions in end-of-life care settings. Music therapy caused significantly stronger reductions of vascular sympathetic tone and, therefore, may be indicated in the treatment of pain and stress-related symptoms in palliative care. Initial self-ratings of pain moderated patients' physiological response and need to be taken into account in clinical practice and future theory building.